Molecular Detection of Virulence Factors Genes for Staphylococcus aureus in Diabetic Foot Ulcers in Iraq - Hussein, Sarah Zghair; Mohammed Saleh , Ghada (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
One of the main complications in patients with Diabetes Mellitus is diabetic foot ulcers (DFUs), a significant and common disease. The wound of a diabetic foot reduces vascular supply and decrease host immune response, facilitating bacterial infection. The pathogen that is most commonly isolated in DFUs is Staphylococcus aureus. The purpose of this work was to identify S. aureus by conventional, biochemical, and molecular detection of the virulence factor genes in DFUs. This case cohort study was directed at Al-Hussein Teaching Hospital (AIsamawa, Iraq) and Medical City/Baghdad Hospital (Baghdad, Iraq) from January to July 2022, and it involved 140 patients with diabetic foot ulcers. Extraction of bacterial DNA from the swab samples was done by ordinary microbiology techniques and was used to achieve polymerase chain reaction (PCR) using specific gene primers (16S ribosomal RNA, mecA, pvl, and α-hly). S. aureus was identified in 34 (24.28%) of the samples. 73 (52.14%) positive cultures of bacterial growth versus 67 (47.85%) show negative results for culturing. The concentration of DNA extracted from 140 swab samples ranged from 10 to 153 ng/µl. 16S rRNA showed that all 34 isolates gave positive results. PCR results were included. 31 (29.8%) of the Staphylococcus aureus were hiding the mecA gene. The α-hly gene was found in 30 (28.8%) of the S. aureus positive samples. The pvl gene was only present in 10 (9.6%) of S. aureus isolates found in DFU’s samples. In DFUs, S. aureus predominated among the microorganisms. All S. aureus isolates included in this investigation had a high prevalence of the 16S rRNA gene. It serves as a genetic marker that can be utilized to confirm isolates of S. aureus. MecA, pvl, and α-hly genes can be found via PCR analysis.